Information asymmetry and financing decisions - Su, Hui Ling (Universiti Malaysia Sarawak (UNIMAS), 2012)
This study explores the relationship between information asymmetry and financing decisions of firms. The sample data includes 598 public-listed firms in Bursa Malaysia, over the sample period from 2005 until 2010. This study relies on firm-level of information, focusing in business context. Information asymmetry is defined as the imbalance amount of information gained between the insiders' management and the outsiders' investor. This study concludes that firms' size, corporate leverage and financial slack could influence the level of information gained among parties. The result and findings in this study shows that total assets has the strongest relationship with the information asymm~try. In addition, total assets could represent internal financing of a firm. The relationship is then followed by financial slack and corporate leverage, respectively. These findings are somehow consistent with the assumption of pecking order theory, showing the preference of firm in deciding to apply internal financing.